Van der Waals hetero-structures of 1H-MoS2 and N-substituted graphene for catalysis of hydrogen evolution reaction - Lakshay Dheer; Satadeep Bhattacharjee; Seung Cheol Lee; Umesh V Waghmare (Materials Research Express, 2020)
First-principles theoretical analysis of the catalytic activity of van der Waals hetero-structures of 1H-MoS _2 and graphene substituted with three chemical types of nitrogen species (i) Graphitic (G), (ii) Pyridinic (Pn) and (iii) Pyrrolic (Pr), for application in catalysis of hydrogen evolution reaction (HER) has been presented. Graphitic and pyrrolic N substituents result in n-type electronic structure, whereas substitution of pyridinic N imparts p-type electronic character to the hetero-structure. Work functions ( φ ) of the hetero-structures suggest that graphitic N-graphene:MoS _2 hetero-structure ( $φ =3.8\,\,{\rm{eV}}$ ) is expected to be effective in catalysing the reduction of H ^+ to evolve H _2 . 1H-MoS _2 monolayer in the hetero-structure contributes by enabling increased H _2 O adsorption and offsetting the band edge energies optimal for the catalytic activity. Near optimum Gibbs free energy of H-adsorption ( ${\rm{Δ }}{G}_{H}$ ) were obtained for graphitic ( ${\rm{Δ }}{G}_{H}$ ∼ 0.29 eV) and pyrrolic ( ${\rm{Δ }}{G}_{H}$ ∼ −0.2 eV) N-graphene:MoS _2 hetero-structures. Our work showcases how catalytic and electronic properties of the N-doped graphene:MoS _2 hetero-structure depends on the chemical identity of N-sites and uncovers a route to 2D hetero-structures with high catalytic activity.